2021
DOI: 10.3389/fpsyt.2021.589949
|View full text |Cite
|
Sign up to set email alerts
|

Initial Evidence for Symptoms of Postpartum Parent-Infant Relationship Obsessive Compulsive Disorder (PI-ROCD) and Associated Risk for Perturbed Maternal Behavior and Infant Social Disengagement From Mother

Abstract: Infant socioemotional development and underlying brain maturation occur primarily within the context of early caregiver-infant relationships. Perinatal research demonstrates detrimental impact of postpartum pathology, including postnatal onset of maternal OCD—on the mother-infant relationship. The present study is the first to examine postnatal onset of a particular dimension of OCD symptoms focusing on close interpersonal relationships (relationship-OCD, i.e., ROCD) within a general population sample. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…These findings are somewhat surprising given the fact that obsessions and compulsions in the postpartum period often revolve around the health and well-being of the newborn child ( 68 , 70 , 75 77 ) and that other studies have demonstrated that mothers experiencing postpartum obsessive-compulsive symptoms are less sensitive in their interaction behavior with their infants compared to healthy mothers ( 65 , 101 ). Indeed, a recent population-based study among Israeli women indicates that maternal postpartum obsessive-compulsive symptoms are associated with poorer mother–child relationship 4 months after delivery ( 102 ). One possible explanation for this unexpected result could be the fact that Ratzoni et al focused on a specific subtype/manifestation of postpartum obsessive-compulsive disorder, namely parent–child relationship obsessive-compulsive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are somewhat surprising given the fact that obsessions and compulsions in the postpartum period often revolve around the health and well-being of the newborn child ( 68 , 70 , 75 77 ) and that other studies have demonstrated that mothers experiencing postpartum obsessive-compulsive symptoms are less sensitive in their interaction behavior with their infants compared to healthy mothers ( 65 , 101 ). Indeed, a recent population-based study among Israeli women indicates that maternal postpartum obsessive-compulsive symptoms are associated with poorer mother–child relationship 4 months after delivery ( 102 ). One possible explanation for this unexpected result could be the fact that Ratzoni et al focused on a specific subtype/manifestation of postpartum obsessive-compulsive disorder, namely parent–child relationship obsessive-compulsive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Women with OCD symptoms displayed lower responsiveness toward their infants than mothers without symptoms. In a sample of 143 mothers, Ratzoni et al (2021) reported higher OCD symptom scores were significantly negatively associated with maternal bonding at 4 months after birth.…”
Section: Impact Of Obsessive-compulsive Disorder On Pregnancy and Out...mentioning
confidence: 92%
“…There is only one scale developed that measures OCD symptoms during the perinatal period, the Perinatal Obsessive-Compulsive Scale (POCS; Lord et al, 2011), which consists of two Likert subscales: a symptom severity subscale and an interference subscale. The fi rst scale to assess symptoms of postpartum Parent-Infant Relationship Obsessive-Compulsive Disorder (PI-ROCD) and its risk for impaired maternal bonding (Ratzoni et al, 2021) was recently published.…”
mentioning
confidence: 99%
“…Studies primarily focus on maternal postpartum depression and anxiety, demonstrating significant prevalence of these conditions (13% and 8.5%, respectively; Goodman et al, 2016;O'Hara & McCabe, 2013). Research further reveals the negative influence of these and other postpartum conditions such as somatization and obsessive compulsive symptoms on observed maternal behavior and associated infant outcomes (Goodman et al, 2016;Murray et al, 2018;Ratzoni et al, 2021). The well documented risks of postpartum depression/anxiety and other symptoms have generated substantial efforts to target these in preventive policy within perinatal healthcare systems worldwide (e.g., Bringing Postpartum Depression Out of the Shadows Act, 2015The United Nations, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Comorbid anxiety has been found to range from 7% for clinical levels of anxiety to 100% for subclinical levels of anxiety, at 4–6 weeks postpartum (Dikmen‐Yildiz et al., 2017; Polachek et al., 2014), with triple co‐morbidity ranging from 2% to 3% (Agius et al., 2016; White et al., 2006). Abundant research has established the adverse impact of postpartum depression, anxiety and other postpartum maternal symptoms on both maternal behavior and infant development (Goodman et al., 2016; Murray et al., 2018; Ratzoni et al., 2021). After controlling for comorbid conditions, one previous study found null effects of PTS‐FC on maternal behavior and infant outcomes (Parfitt et al., 2013).…”
Section: Introductionmentioning
confidence: 99%